1996
DOI: 10.1053/jhep.1996.v24.pm0008707287
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution of transcripts for tissue inhibitor of metalloproteinases 1 and 2 in human hepatocellular carcinomas

Abstract: The cellular distribution of tissue inhibitor of metalloproteinases (TIMP)-1, and TIMP-2 was studied by using in situ hybridization in surgically removed human hepatocellular carcinomas (HCCs) and cholangiocellular carcinomas (CCCs). The purpose of this study was to characterize the protein involvement of TIMPs in the development of HCCs and CCCs. All HCCs and CCCs expressed TIMPs. The distribution of transcripts for TIMPs in the tumors was mostly homogeneous. Expression of TIMP in cancer cells was more intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In 2009, Altadill and his colleagues reported that overexpressed MMP-1 by fibroblast cells is correlated with poor prognosis (19), supported by the findings that overexpressed MMP-1 was associated with an elevated metastasis capacity of the HCC cells (53,54). Altadill and his colleagues also reported that overexpressed TIMP1 by stromal cells is correlated with shortened overall survival period (19), and accordingly TIMP-1 overexpression was reported to be associated increased invasive and metastatic capacity of the HCC cells (55,56). In the near future, further analysis of TIMP1 genotype/phenotype may provide further evidence for evaluating the contribution of combined genotypes of MMP-1 and TIMP1 to the carcinogenesis of HCC.…”
Section: Discussionmentioning
confidence: 91%
“…In 2009, Altadill and his colleagues reported that overexpressed MMP-1 by fibroblast cells is correlated with poor prognosis (19), supported by the findings that overexpressed MMP-1 was associated with an elevated metastasis capacity of the HCC cells (53,54). Altadill and his colleagues also reported that overexpressed TIMP1 by stromal cells is correlated with shortened overall survival period (19), and accordingly TIMP-1 overexpression was reported to be associated increased invasive and metastatic capacity of the HCC cells (55,56). In the near future, further analysis of TIMP1 genotype/phenotype may provide further evidence for evaluating the contribution of combined genotypes of MMP-1 and TIMP1 to the carcinogenesis of HCC.…”
Section: Discussionmentioning
confidence: 91%
“…52 Overexpression of TIMP-1 but underexpression of TIMP-2 and -3 have been reported to be associated with invasion and metastasis in hepatocellular carcinoma. 25,53,54 Early studies using recombinant TIMPs or basic gene transfer system (plasmids or retrovirus) have demonstrated that inhibition of MMPs by TIMPs blocks both tumor growth and local invasion. However, the use of TIMPs in clinical trials has proven largely disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…A balance of TIMPs and MMPs can control the local activities of MMPs in tissues to avoid the degradation of ECM proteins; however, a disturbed balance of TIMPs and MMPs is known to occur in malignant tumors, which leads to cancer cell migration and invasion. Study has shown that TIMP-1/-2 and MMP-9 all play crucial roles in the tumor cell growth and invasion of hepatocellular carcinomas [25,26]. 11-epi-Sinulariolide acetate was originally isolated from cultured-type soft coral Sinularia flexibilis, and has been reported to exert anti-invasion and anti-migration effects on hepatoma HA22T cells [27].…”
Section: Discussionmentioning
confidence: 99%